Binder, pole piece, preparation method and application of pole piece and electrochemical device

By using components such as poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonate) and citric acid in the binder, the problems of insufficient bonding strength and poor electronic conductivity of the composite binder are solved, and the high cycle performance and rate performance of the battery are achieved.

CN119799243APending Publication Date: 2025-04-11SHANGHAI SHANSHAN TECH CO LTD

Patent Information

Application Number
CN202411998026.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

In the prior art, the insufficient bonding force of the composite adhesive has to be improved, and the poor electronic conductivity of the silicon-based material adhesive has caused the ionic conductivity and electronic conductivity to be unable to be taken into account at the same time, resulting in poor rate performance of the battery.

Method used

Poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonate) is used as the base component of the binder, and citric acid and alcohol compounds are added. Through the coordinated use of citric acid and alcohol compounds, the molecular chain of poly(3,4-ethylenedioxythiophene) is changed from a curled conformation to a linear conformation, thereby improving the electronic conductivity and adhesion of the binder.

Benefits of technology

The adhesive has better adhesion, electronic conductivity and better ionic conductivity, and the obtained battery has better cycle performance and rate performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005225860540000061
    Figure BDA0005225860540000061
  • Figure BDA0005225860540000071
    Figure BDA0005225860540000071
  • Figure BDA0005225860540000081
    Figure BDA0005225860540000081
Patent Text Reader

Abstract

The invention discloses a binder, a pole piece, a preparation method and application of the pole piece and an electrochemical device. The binder comprises the following components: poly (3, 4-ethylenedioxythiophene)-poly (styrene sulfonate), citric acid and an alcohol compound. The binder disclosed by the invention has relatively good binding power and relatively good electronic conductivity, and can give consideration to relatively good electronic conductivity and ionic conductivity. The expansion rate of the pole piece prepared from the binder disclosed by the invention is relatively low. The battery prepared from the binder disclosed by the invention has relatively good cycle performance and rate capability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a binder, a pole piece, a preparation method thereof, an application thereof and an electrochemical device. Background Art

[0002] Lithium-ion batteries (LIBs) with high energy density and long cycle life have become an ideal choice for a variety of new automobiles and consumer electronics. As the most widely used anode material in LIBs, graphite anode has almost reached the theoretical level (372 mAh g -1 ), thus limiting the development of LIBs. Therefore, it is urgent to find alternative anode materials for the next generation of LIBs.

[0003] Silicon (Si) material has a high theoretical specific capacity (4200mAhg -1 ) has received widespread attention. However, during the lithiation / delithiation process, Si particles undergo a huge volume change (≥300%), resulting in particle breakage, reduced conductivity, and continuous generation of the SEI layer, which leads to a rapid decline in capacity and cycle life. Polymers with polar groups are widely used as silicon anode binders because they can bind to Si particles through hydroxyl functional groups, thereby inhibiting the volume expansion of silicon.

[0004] One-dimensional linear polymer binders such as sodium alginate (SA), polyacrylic acid (PAA), sodium carboxymethyl cellulose (CMC) can easily slide on the Si surface during electrochemical cycles and have difficulty adapting to the mechanical stress caused by the volume expansion / contraction of silicon during the cycle. Three-dimensional binders have a stable three-dimensional network structure and show higher strength. As a binder, it can effectively eliminate the mechanical stress caused by volume changes during charge and discharge. However, due to the low electrical conductivity of silicon particles themselves and the electrical insulator properties of polymer binders, conductive agents are usually added to improve the conductivity of silicon-based anode materials.

[0005] Traditional granular carbon-based conductive agents usually do not contain functional groups and are only connected to the binder and silicon particles through fragile hydrogen bonds. During the cycle, silicon can easily lose its connection with the conductive carbon due to volume changes, resulting in the inactivation of active components and capacity decay. The use of water-soluble conductive agents with rich functional groups can not only significantly improve the contact interface between the conductive carbon agent, binder and silicon nanoparticles, but also maintain the more important bonding between the conductive agent, binder and silicon nanoparticles through in-situ crosslinking.

[0006] Chinese patent application CN110890545A discloses a composite binder prepared by cross-linking PEDOT:PSS with CMC, which has better mechanical properties and conductive properties. When the composite binder is used to prepare the silicon-based negative electrode of lithium-ion batteries, the functional groups in the binder can effectively bond with silicon, thereby improving the bonding strength with the silicon-based material and improving the structural stability. However, the bonding strength of the composite binder needs to be improved, resulting in the cycle performance of the resulting battery still needs to be improved.

[0007] Chinese patent application CN115224278A discloses a flexible conductive adhesive, which forms a three-dimensional network structure by cross-linking polyethylene imine (BPEI) and polyacrylamide (PAM), increasing the contact points between the adhesive and the silicon-containing active material, while limiting the volume expansion of silicon and improving the adhesion of the adhesive. This adhesive has high conductivity and thermal stability, can provide a stable conductive network, and maintain a complete electrode structure, with excellent electrochemical performance.

[0008] In the prior art, various methods are used to prepare silicon-based material binders, but the prepared materials still have low electronic conductivity, resulting in the problem that ionic conductivity and electronic conductivity cannot be taken into account at the same time, thereby limiting the rate performance of the battery to a certain extent. Summary of the invention

[0009] The technical problem to be solved by the present invention is to overcome the defects in the prior art that the composite adhesive has insufficient bonding force, resulting in the cycle performance of the battery assembled therefrom still needs to be improved, and the silicon-based material adhesive still has poor electronic conductivity, resulting in the inability to take both ionic conductivity and electronic conductivity into account, resulting in poor rate performance of the battery assembled therefrom, and to provide a bonding agent, pole piece, preparation method, application and electrochemical device thereof. The bonding agent of the present invention has better bonding force and better electronic conductivity, and can take both better electronic conductivity and ionic conductivity into account. The pole piece made from the bonding agent of the present invention has a lower expansion rate. The battery made from the bonding agent of the invention has better cycle performance and rate performance.

[0010] The present invention solves the above technical problems through the following technical solutions.

[0011] The invention provides a binder, which comprises the following components: poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonate), citric acid and an alcohol compound.

[0012] In the present invention, the poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonate) is blended by poly(3,4-ethylenedioxythiophene) (PEDOT) having conductive properties and polystyrene sulfonic acid (PSS) having solubility and stability. In the poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonate), the mass ratio of poly(3,4-ethylenedioxythiophene) to polystyrene sulfonic acid can be (3-7):1, for example, 5:1.

[0013] In the present invention, the alcohol compound is preferably a C1-C8 alcohol compound, more preferably a C1-C4 alcohol compound, and even more preferably one or more of methanol, ethanol, isobutanol and isopropanol, such as isopropanol.

[0014] In the present invention, the mass ratio of the citric acid to the poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonate) may be 1:(0.5-5), preferably 1:(0.8-3), for example 1:1.6, 1:0.87, 1:2.17 or 1:2.5.

[0015] In the present invention, the mass volume ratio of the poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonate) and the alcohol compound may be (200-500) mg:1 mL, preferably (300-400) mg:1 mL, for example 350 mg:1 mL, 370 mg:1 mL or 390 mg:1 mL.

[0016] In the present invention, the mass volume ratio of the citric acid to the alcohol compound may be (100-300) mg:1 mL, preferably (200-250) mg:1 mL, such as 230 mg:1 mL, 250 mg:1 mL or 280 mg:1 mL.

[0017] In the present invention, the binder preferably further comprises an ion conductive polymer. The ion conductive polymer preferably comprises polyethylene oxide (PEO) and / or polyethylene imine (PEI), such as polyethylene imine (PEI). Wherein, the mass ratio of the poly (3,4-ethylenedioxythiophene) -poly (styrene sulfonate) to the ion conductive polymer may be (0.1-0.5):100, preferably (0.15-0.4):100, such as 0.185:100, 0.25:100 or 0.3:100.

[0018] The mass ratio of the citric acid to the ion conductive polymer may be (0.05-0.4):100, preferably (0.1-0.3):100, such as 0.115:100, 0.2:100 or 0.25:100.

[0019] In the present invention, the researchers found during the research and development process that the synergistic use of citric acid and alcohol compounds can change the molecular chain of poly(3,4-ethylenedioxythiophene) from a curled conformation to a linear conformation, thereby improving the electronic conductivity of poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonate).

[0020] The present invention also provides a method for preparing the adhesive as described above, which comprises the following steps: mixing the components of the adhesive.

[0021] The present invention also provides a method for preparing a pole piece, which comprises the following steps: coating a pole piece slurry on at least one surface of a current collector and annealing the pole piece slurry; the pole piece slurry comprises the aforementioned binder, silicon-based material and solvent; and the annealing temperature is 150-250°C.

[0022] In the present invention, the type of the silicon-based material can be conventional in the art, such as silicon nanoparticles. The D50 of the silicon-based material can be 100-200 nm, such as 180 nm.

[0023] In the present invention, the mass ratio of "the sum of the masses of poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonate) and citric acid" in the binder to the silicon-based material can be 1:(2-10), preferably 1:(2.2-9.5), for example 1:2.3, 1:4, 1:4.5, 1:5.6, or 1:9.

[0024] In the present invention, the mass ratio of the poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonate) and the silicon-based material in the binder may be 1:(2-20), preferably 1:(3-15), for example 1:3.8, 1:6.5, 1:14.6, 1:12 or 1:4.8.

[0025] In the present invention, the mass ratio of the citric acid to the silicon-based material in the binder may be 1:(5-25), preferably 1:(6-24), for example 1:6.1, 1:8, 1:10.4, 1:15, 1:20 or 1:23.5.

[0026] In the present invention, when the binder further includes an ion conductive polymer, the mass ratio of the ion conductive polymer to the silicon-based material may be 1:(5-30), preferably 1:(7-27), for example 1:10, 1:12, 1:15, 1:20 or 1:25.

[0027] In the present invention, the type of the solvent may be any conventional solvent in the art that can dissolve the components of the adhesive, such as water and / or isopropyl alcohol.

[0028] In the present invention, the type of the current collector may be conventional in the art, such as copper foil.

[0029] In the present invention, the coating thickness may be 100 μm.

[0030] In the present invention, the annealing treatment is preferably performed in a tube furnace.

[0031] In the present invention, the temperature of the annealing treatment is preferably 180-220°C, such as 200°C.

[0032] In the present invention, the annealing treatment time may be 1-5 hours, for example 2.5 hours.

[0033] In the present invention, the method for preparing the electrode slurry preferably includes the following steps: (1) adding citric acid to a mixture of poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonate) and an alcohol compound, then adding a silicon-based material, and then adding a first solvent to obtain a first slurry; (2) stirring and mixing the first slurry, coating it on at least one surface of a current collector, and annealing it.

[0034] In the present invention, the method for preparing the pole piece slurry more preferably includes the following steps: (1) adding citric acid to a mixture of poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonate) and an alcohol compound, then adding a silicon-based material, and then adding a first solvent to obtain a first slurry; (2) stirring and mixing the first slurry, coating it on at least one surface of a current collector, and annealing to obtain a first pole piece; (3) mixing the first pole piece and an ion conductive polymer solution, and drying.

[0035] The first solvent is preferably water, and the volume ratio of the first solvent to the alcohol compound having 1 to 8 carbon atoms is preferably (3-7):1, for example, 5:1.

[0036] The first slurry is preferably stirred for 6 hours at 25° C. The stirring speed is preferably 300-700 rpm, such as 500 rpm.

[0037] Wherein, after the coating and before the annealing treatment, a drying step is preferably performed. The drying operation can be conventional in the art, such as drying in a vacuum drying oven. The drying temperature can be 50-70° C., such as 60° C. The drying time can be 7-9 hours, such as 8 hours.

[0038] The mass concentration of the ion conductive polymer solution is preferably 0.05wt%-0.15wt%, such as 0.1wt%. The ion conductive polymer solution preferably includes an ion conductive polymer and a second solvent. The second solvent is preferably ethanol or isopropanol. The mass ratio of the ion conductive polymer to the second solvent is preferably (0.05-0.15):100, such as 0.1:100.

[0039] The mixing method may be soaking. The mixing time may be 20-40 seconds, for example 30 seconds.

[0040] The drying operation may be conventional in the art, such as drying in a vacuum drying oven. The drying temperature may be 50-70° C., such as 60° C. The drying time may be 40-50 h, such as 48 h.

[0041] The present invention also provides a pole piece, which is manufactured by the pole piece manufacturing method as described above.

[0042] The present invention also provides a use of the aforementioned binder or the aforementioned pole piece in an electrochemical device.

[0043] The present invention also provides an electrochemical device, which comprises the pole piece as described above.

[0044] In the present invention, the electrochemical device is preferably a lithium-ion battery.

[0045] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0046] The reagents and raw materials used in the present invention are commercially available.

[0047] The positive and progressive effects of the present invention are:

[0048] The present invention uses poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonate) as the basic component of the binder, and the addition of citric acid can improve the binding force and ion conductivity of the binder; the citric acid and alcohol compounds can be used in conjunction to improve the electronic conductivity of the binder. Therefore, the binder of the present invention has better binding force, better electronic conductivity, and can take into account better ion conductivity and electronic conductivity. The battery made from the binder has better cycle performance and rate performance. DETAILED DESCRIPTION

[0049] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0050] In the following examples or comparative examples, PEDOT-PSS represents poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonate), the specification model is Clevios PH1000, the mass ratio of PEDOT to PSS is 5:1, purchased from Heraeus; IPA represents isopropanol; CA represents citric acid; PEI represents polyethyleneimine, Mw=25000 gmol-1 , purchased from Sigma-Aldrich.

[0051] The components and amounts of the binders and the amounts of the silicon-based materials of Examples 1-5 and Comparative Examples 1-2 and Comparative Examples 4-6 are shown in Table 1 below.

[0052] Table 1

[0053]

[0054]

[0055] Note: In Table 1, “ / ” means that the component is not added.

[0056] The preparation method of the pole piece in Examples 1-5 and Comparative Examples 1-2 and Comparative Examples 4-6 comprises the following steps:

[0057] (1) Using an electronic balance, 370 mg of PEDOT-PSS (specification: Clevios PH1000, purchased from Heraeus) and 1 mL of IPA were weighed into a glass bottle, and then 230 mg of CA was added, and then 1.4 g of nano-silicon powder (180 nm) was added, and finally 5 mL of deionized water was added as the first solvent to obtain a first slurry.

[0058] (2) Stir the prepared first slurry at 25°C for 6 hours at a rotation speed of 500 rpm; then use a scraper to evenly apply the stirred first slurry on the copper foil with a coating thickness of 100 μm; then put it into a vacuum drying oven at 60°C for 8 hours to remove moisture; then transfer it to a tube furnace and anneal it at 200°C in vacuum for 2.5 hours to obtain the first electrode;

[0059] (3) Weigh 0.2 g PEI (Mw = 25000 gmol -1 , purchased from Sigma-Aldrich), and then add 200g of ethanol solvent, stir evenly to obtain a PEI solution, place the first electrode obtained in step (2) in the obtained PEI solution and soak for 30 seconds, and finally transfer it to a vacuum drying oven at 60°C and dry it for 48h.

[0060] Comparative Example 3 Preparation Method of Pole Sheet

[0061] (1) 300 mg of sodium carboxymethyl cellulose (CMC) was weighed using an electronic balance, and then 300 mg of acetylene black (AB) was added, and then 2.4 g of nano-silicon powder was added. After the three materials were ground and mixed evenly, 300 mg of N-methyl-2-pyrrolidone (NMP) solvent was added, and then stirred with a magnetic bar at room temperature for 12 hours. Then, the stirred slurry was evenly coated on the copper foil using a scraper, and the coating thickness was 100 μm;

[0062] (2) Then place the above sample in a vacuum drying oven at 60°C and dry for 8 hours to remove moisture.

[0063] Effect Example 1

[0064] The pole piece prepared in the above embodiment or comparative example is the positive electrode of the half-battery, the metal lithium sheet is the negative electrode, the separator is a polypropylene (PP) film, and the electrolyte is a 1 mol / L LiPF6 solution (the solvent is ethylene carbonate (EC) / ethyl methyl carbonate (EMC) = 1:1, and the additive is 20wt% fluoroethylene carbonate (FEC)); the button battery is tested for performance, and the test conditions are: the voltage range is 0.005-2.0V, and the first cycle coulomb efficiency, cycle performance (25°C, 1C / 1C cycle, the number of cycles at which the capacity decays to 80%), and rate performance (25°C, 3.5C discharge capacity retention rate) are tested respectively;

[0065] In addition, the electrode sheets prepared in the embodiments and comparative examples were subjected to a full charge expansion test: (thickness of the electrode sheet when the button cell is fully charged to 100% SOC - thickness of the electrode sheet before the test) / thickness of the electrode sheet before the test × 100%. The test results are shown in Table 2.

[0066] Adhesion test: The adhesion between the adhesive and the copper foil in the pole pieces prepared in the embodiment and the comparative example was tested using a universal testing machine. The test results are shown in Table 2.

[0067] Electronic conductivity test: First, the adhesive films obtained in the embodiment and the comparative example are deposited on clean glass (the components of the adhesive can be mixed), a groove is scratched on the film with the tip of tweezers, and the step height of the groove is measured by a step meter to obtain the thickness of the film sample, which is recorded as t; then, the adhesive films obtained in the embodiment and the comparative example are prepared on clean glass (the components of the adhesive can be mixed), and the square resistance of each film sample is measured by four-probe, which is recorded as Rsr; Electronic conductivity σ=(Rsr×t) -1 .

[0068] Ionic conductivity test: The adhesive prepared in the embodiment and the comparative example (the components of the adhesive can be mixed) is coated on a copper foil, dried at 85°C, and the thickness (L) and area (A) of the adhesive film are measured after peeling; then the membrane is made into a symmetrical battery, with the other side being a copper foil, and no separator is added in the middle. After liquid injection, it is left to stand for 24 hours, and then hot pressed to make the interface fully contact (0.2Mpa, 60°C, 1min); then an EIS test is performed: frequency range 1-500KHz, amplitude 5mV, ohmic impedance is recorded as R; ionic conductivity σ=L / (R×A).

[0069] The test results are shown in Table 2.

[0070] Table 2

[0071]

[0072]

[0073] From Table 2 we can see that:

[0074] Compared with comparative examples 1-6, the binder of embodiment 1-5 has better bonding force. The electrode sheet made by the binder has a lower full-charge expansion rate. The battery made by the binder can take into account better ionic conductivity and electronic conductivity, and has better cycle performance, rate performance and first-cycle coulomb efficiency.

[0075] The electrochemical performance of Example 1 of the present invention is slightly worse than that of Example 2 because the amount of silicon-based material used in Example 1 is small, resulting in a small amount of citric acid remaining, which reduces the conductivity of the obtained silicon-carbon composite material;

[0076] The electrochemical performance of Example 3 is slightly worse than that of Example 2 because the amount of silicon-based material used in Example 3 is relatively large, resulting in it not being completely coated by the conductive adhesive, and the adhesive of the adhesive is slightly poor and easily falls off from the current collector;

[0077] The electrochemical performance of Comparative Examples 2 and 5 is poorer than that of Example 2 because the annealing temperature in Comparative Example 2 during the electrode preparation process is too low, and PEDOT-PSS and CA cannot completely cover the silicon-based material; the annealing temperature in Comparative Example 5 is too high, resulting in the complete decomposition of PEDOT-PSS and inability to effectively cover.

[0078] In addition, the electrochemical performance of Comparative Example 1 is poorer than that of Example 2 because CA is not added to the binder of Comparative Example 1, resulting in a lower bonding force between the binder and the current collector, and the first efficiency of the obtained battery is lower;

[0079] The electrochemical performance of Comparative Example 6 is poorer than that of Example 2 because the ion transfer rate is reduced in Comparative Example 1 due to the lack of immersion in the PEI solution, resulting in poor rate performance;

[0080] The electrical properties and bonding strength of Comparative Example 3 are relatively poor, indicating that the conductive binder-coated nano-silicon synthesized by this method has better performance than the combination of conductive agent, binder and active material in the prior art.

Claims

1. A binder, characterized in that: The binder comprises the following components: Poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonate), citric acid and alcohol compounds.

2. The adhesive according to claim 1, characterized in that The binder also includes an ion-conductive polymer; Wherein, the ion conductive polymer preferably includes polyethylene oxide and / or polyethylene imine, such as polyethylene imine.

3. The adhesive according to claim 1, characterized in that The binder meets one or more of the following conditions: A. The alcohol compound is a C1-C8 alcohol compound, preferably a C1-C4 alcohol compound, more preferably one or more of methanol, ethanol, isobutanol and isopropanol, such as isopropanol; B. The mass ratio of the citric acid to the poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonate) is 1:(0.5-5), preferably 1:(0.8-3), for example 1:1.6, 1:0.87, 1:2.17 or 1:2.5; C. The mass volume ratio of the poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonate) to the alcohol compound is (200-500) mg:1 mL, preferably (300-400) mg:1 mL, for example 350 mg:1 mL, 370 mg:1 mL or 390 mg:1 mL; D. The mass volume ratio of the citric acid to the alcohol compound is (100-300) mg:1 mL, preferably (200-250) mg:1 mL, for example 230 mg:1 mL, 250 mg:1 mL or 280 mg:1 mL.

4. The adhesive according to claim 2, characterized in that The binder meets one or more of the following conditions: A. The mass ratio of the poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonate) to the ion conductive polymer is (0.1-0.5):100, preferably (0.15-0.4):100, for example 0.185:100, 0.25:100 or 0.3:100; B. The mass ratio of the citric acid to the ion conductive polymer is (0.05-0.4):100, preferably (0.1-0.3):100, for example 0.115:100, 0.2:100 or 0.25:

100.

5. A method for preparing the adhesive according to any one of claims 1 to 4, characterized in that: The method comprises the following steps: mixing the various components of the binder.

6. A method for preparing a pole piece, characterized in that: The preparation method comprises the following steps: coating the pole piece slurry on at least one surface of the current collector and annealing the pole piece slurry; the pole piece slurry comprises a binder, a silicon-based material and a solvent as described in any one of claims 1 to 4; and the annealing temperature is 150-250°C.

7. The method for preparing a pole piece according to claim 6, characterized in that: The method for preparing the pole piece satisfies one or more of the following conditions: A. The type of the silicon-based material is silicon nanoparticles; B. The D50 of the silicon-based material is 100-200 nm, for example 180 nm; C. The mass ratio of "the sum of the mass of poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonate) and citric acid" in the binder to the silicon-based material is 1:(2-10), preferably 1:(2.2-9.5), for example 1:2.3, 1:4, 1:4.5, 1:5.6, or 1:9; D. The mass ratio of the poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonate) to the silicon-based material in the binder is 1:(2-20), preferably 1:(3-15), for example 1:3.8, 1:6.5, 1:14.6, 1:12 or 1:4.8; E. The mass ratio of the citric acid to the silicon-based material in the binder is 1:(5-25), preferably 1:(6-24), for example 1:6.1, 1:8, 1:10.4, 1:15, 1:20 or 1:23.5; F. When the binder further includes an ion conductive polymer, the mass ratio of the ion conductive polymer to the silicon-based material is 1:(5-30), preferably 1:(7-27), for example 1:10, 1:12, 1:15, 1:20 or 1:25; G. The type of the solvent is water and / or isopropanol; H. The annealing temperature is 180-220°C, for example 200°C; I. The annealing time is 1-5h, for example 2.5h.

8. A pole piece, characterized in that: It is prepared by the method for preparing a pole piece as claimed in claim 6 or 7.

9. A binder as claimed in any one of claims 14, or use of the pole piece as claimed in claim 8 in an electrochemical device.

10. An electrochemical device, characterized in that: It comprises the pole piece as claimed in claim 9.

Citation Information

Patent Citations

  • PEDOT: PSS / CMC composite binder and preparation method and application thereof

    CN110890545A

  • Conductive composite binder for silicon anode, preparation method and lithium ion battery

    CN115224278A

Cited By

  • Silicon-based negative electrode material and preparation method and application thereof

    CN120511267A